An Experimental Study of the Social Dimension of Land Consolidation Using Trust Games and Public Goods Games - Matsatso Tepnadze; Walter Timo de Vries; Pamela Duran Diaz; Quji Bichia (Land, 2022)
Most land consolidation projects envisage reducing fragmentation and aim at increasing productivity, land use efficiency, and competitiveness of rural areas. However, recent insights suggest that social aspects are crucial as well. Hence, a critical assessment of the conditions under which land consolidation can be socially beneficial is necessary. This article aims to identify values and qualitative indicators to measure social preferences and to assess whether one can optimize decision support tools for land consolidation projects with such indicators. Based on an exploratory and concept-centric qualitative literature review, we propose game applications from experimental economics to measure empirical indicators of social capital. The games help to disclose conflicting social preferences and enable a more accurate response to public policy programs/interventions. This is achieved by assessing commonly shared norms of trust, reciprocity, and cooperation within and across social groups in a targeted area. We posit, however, the disparity among bonding, bridging, and linking dimensions of a social capital could have a differential effect on land consolidation instruments. This experimental method applied in Kakheti, Georgia reveals that 1. the farmer communities have varying combinations of bonding, bridging, and linking social capital; 2. the local farmer societies are the archetype of the collaborative model and sharing economy; 3. only a few municipalities show the highest potential for sustainably managing land consolidation projects. Hence, applying economic games that explore social scenarios helps to derive more favourable solutions for land consolidation.